Vitamin D Effects on Glycemic and Cardiometabolic Profiles in PCOS: A Meta-Analysis - Adityo Prabowo (Asian Journal of Health Research, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is a multifaceted endocrine disorder characterized by hyperandrogenism and ovulatory dysfunction. Beyond reproductive consequences, PCOS is fundamentally associated with metabolic dysregulation, including insulin resistance and dyslipidaemia. High rates of Vitamin D deficiency in this population suggest a link to these metabolic characteristics. This systematic review and meta-analysis assessed the efficacy of Vitamin D supplementation compared to placebo on glycemic control markers (HOMA-IR, fasting glucose) and cardiometabolic risk profiles in women with PCOS.   Material and Methods: A comprehensive search was executed across PubMed, Europe PMC, Open Alex, and Science Direct (2015- 2025) following PRISMA 2020 guidelines. The review included Randomized Controlled Trials (RCTs) involving women diagnosed via Rotterdam or NIH criteria. Quality was assessed using the Cochrane Risk of Bias 2.0 tool, with quantitative synthesis performed using appropriate statistical models.    Results: Fourteen RCTs were synthesized. The meta-analysis indicated that Vitamin D supplementation significantly improved insulin resistance, with a pooled Mean Difference in HOMA-IR of -0.61 (95% CI: -0.81 to -0.41; p < 0.001). Furthermore, a consistent decrease in serum triglycerides was observed (MD = -17.12 mg/dL; 95% CI: -18.60 to -15.64; p < 0.001). Secondary outcomes suggested improvements in ovulation and oxidative stress biomarkers and visceral adiposity.    Conclusion: Vitamin D supplementation demonstrates a beneficial therapeutic profile in women with PCOS, providing substantial advantages in enhancing insulin sensitivity and lipid metabolism. Thus, it appears to be a safe, effective adjuvant strategy for reducing long-term cardiometabolic risk.